Evaluation for equitable development results (UNICEF, 2011)
This document is made up of a range of Evaluation Working Papers (EWP) focused on evaluation for equitable development. Put together by eval uation specialists they present strategic evaluation findings, lessons learned and innovative approaches and methodologies. Part 1:Evaluatio n and equity Evaluation to accelerate progress towards equity, social justice and human rights 2 Human rights and gender equality in evaluat ion 13 When human rights is the starting point for evaluation 25 Stren gthening Equity- focused evaluations through insights from feminist th eory and approaches 39 Decolonizing evaluation in a developing world. Implications and cautions for Equity-focused evaluations 59 Part 2: Me thodological implications for Equity-focused evaluations Methodologica l issues to design and implement equity-focused evaluations 86 Develop mental evaluation for Equity-focused evaluations 102 Systems thinking and Equity-focused evaluations 115 Methodological challenges in using programme theory to evaluate pro-poor and equity-focused programmes by Patricia Rogers, Royal Melbourne Institute of Technology University a nd Richard Hummelbrunner, Independent consultant 142 Case Study and eq uity in Evaluationby Saville Kushner, University of the West of Englan 172 Values-Engaged Evaluationsby Jennifer Greene, University of Illin ois at Urbana-Champaign 192 Part 3: Examples of Equity-focused evaluat ions Evaluating the contribution of UNDP to equity-focused public poli cies in Brazil and China 210 Using a human rights approach to evaluate ILO’s discrimination strategy 222 CONEVAL experience in evaluating in terventions for Indigenous populations in Mexico 244 UNICEF supported evaluations with elements of equity-focused evaluations 258